Study of the Nuclear Structure for 38Ar, 59Co, 124Sn, 146Nd, 153Eu and 203Tl Target Nuclei Used in Fabrication the Nuclear Batteries - Alaamery, Samaa Samir; Kareem, Ali A. (Iraqi Journal of Physics, 2020)
The nuclear structure of 38Ar, 59Co, 124Sn, 146Nd, 153Eu and 203Tl target nuclei used in technology for nuclear batteries have been investigation, in order that, these nuclei are very interesting for radioisotope thermo-electric generator (RTG) space studies and for betavoltaic battery microelectronic systems. The single particle radial density distribution, the corresponding root mean square radii (rms), neutron skin thicknesses and binding energies have been investigated within the framework of Hartree-Fock Approximation with Skyrme interaction. The bremsstrahlung spectrums produced by absorption of beta particles in betavoltaic process and backscattered photons spectrum have also been calculated. All obtained results compared with available experimental data.